SMC controller design for DC motor speed control applications and performance comparison with FLC, PID and PI controllers - AK, AYÇA (My University, 2023)
Sliding Mode Control (SMC), which is built on the variable structure control (VSC) algorithm, is a robust and non-linear control method that can provide the desired dynamic behaviour for the system to be controlled despite external and internal disturbances and uncertainties. The SMC method can be successfully implemented in the control of high-dimensional nonlinear systems operating under uncertain conditions due to its high accuracy and simplicity of application. In this MATLAB/Simulink based study; the SMC method is applied to the speed control of a DC motor. For this purpose, firstly, the dynamic model of DC motor and the mathematical model of the SMC have been designed and transferred to the Simulink environment. The performance of the SMC system has been examined under different loading conditions applied to the motor. In addition, the effects of changing the SMC parameters on the sliding surface, chattering and motor dynamic behaviours have been investigated. In order to evaluate the success of the SMC topology in DC motor control application, Fuzzy Logic Control, PID and PI control methods were applied on the same motor and their performances were compared with the SMC method.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Control and Systems Engineering; Physical Sciences; Computer Networks and Communications; DC motor; Fuzzy logic; PID control; Sliding mode control